Measurement of Radon-222 Concentration Levels in Brands of Sachet Drinking-Water Produce in Dutsin-Ma Local Government Area (LGA) of Katsina State, Nigeria - Baraya, Jamilu Tijjani; Sani, Mujahid Hassan; Joshua, Josiah (Journal of Asian Scientific Research, 2020)
The purpose of this study is to measure the concentration levels of radon-222 from seven (7) water samples collected at different sachet drinking-water companies located within Dutsin-Ma LGA using Liquid Scintillation Counter. The levels of radon-222 found to range from (11.69 to 13.04 ), and (9.23 to 11.19 ) with mean values of 12.37 and 10.18 for borehole and earth-dam sources respectively. The results found are compared with the world average maximum contaminant level (MCL) of 10 set by WHO and it was discovered that 86% of the samples are below the value and 100% of the samples are below the WHO recommended reference level of 100 . Annual effective doses due to ingestion of radon in water for three (3) categories of people were estimated from the measured radon concentrations and their mean values were found to be (0.090, 0.181 and 0.632) in borehole water and (0.074, 0.149, and 0.520) in surface water (earth-dam) for adults, children and infants respectively. Most of the mean values of the annual effective doses were below the recommended level of 0.1 set by WHO. Therefore, it is recommended that the inhabitants of Dutsin-Ma LGA should always drink the sachet water produce by the companies irrespective of it source.